Storm surge modelling along the east coast of Bicol Region using ADCIRC - Fernandez, Jay-ar R.
Severe storms have been devastating the Philippines, the Bicol Region in particular, for the longest time now. The risks posed by storm surge have not been fully realized until lately, when Super Typhoon Haiyan (Yolanda) ravaged the Visayas Region in 2013. People were not aware of the hazard and how to make their lives less vulnerable from the disaster. It is then timely to investigate this phenomenon. Numerical modeling of storm surge using ADCIRC is performed on the east coast of Bicol region and the results were validated using actual tide readings from the National Mapping and Resource Information Agency (NAMRIA). Analysis of Variance (ANOVA) shows that astronomical tides and tides recorded at observation points do not show any significant difference. From this, it is said that the model is calibrated. Upon running Typhoon Sening (Joan, 1970) which produced roughly 0.4 m of surge, the model was proven to be valid upon comparing results with that of NAMRIA. Moreover, runs on Typhoon Reming were also conducted and it produced up to 0.96 m surge heights. Simulation results also point the Municipalities of Presentacion, San Jose, Tigaon and Sangay in Camarines Sur; Tiwi, Malinao, Tabaco City, Malilipot, Bacacay, Sto. Domingo, Rapu-Rapu and Legaspi City in Albay; and San Andres in Catanduanes as highly vulnerable areas against storm surge. Whenever there are storms that might pass along these areas, with characteristics that are extremely similar with the two typhoons simulated, roughly similar storm surge heights are expected.